Florida's Class Size Amendment and Co-Teaching: An Uneasy Partnership - Lenford C. Sutton; Phyllis Jones; Julia White (Educational Considerations, 2008)
For nearly four decades, school finance has become progressively more central in school reform efforts aimed at improving student performance.
Keywords: Florida’s Class Size Amendment (CSA); implementation; challenges; teaching; benefits; funding